1997
DOI: 10.1046/j.1365-3059.1997.d01-58.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combinations amongst genes Lr13, Lr34 and Lr37 on components of resistance in wheat to leaf rust

Abstract: Gene pyramiding is a breeding strategy whereby host resistance genes are combined together with the objective of prolonging their usefulness in crops such as wheat (Triticum aestivum) for resistance to leaf rust caused by Puccinia recondita f.sp. tritici. When genes are combined they often give reactions different from those given by each component gene alone. Effects of gene combinations in lines Lr13 + Lr34 (T34-13), Lr13 + Lr37 (T13-37) and Lr34 + Lr37 (T34-37) were compared with those of the single gene li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 24 publications
11
55
1
Order By: Relevance
“…Lr34 is widely recognized as reducing severity or receptivity as measured by the percentage of infected leaf area and accounts for 20%-50% of the phenotypic variation in various reports [4, [29][30][31][32][33]. In this study, the effect of the rust resistance QTL at the Lr34 locus was consistent with previous reports [4,34].…”
Section: Discussionsupporting
confidence: 91%
“…Lr34 is widely recognized as reducing severity or receptivity as measured by the percentage of infected leaf area and accounts for 20%-50% of the phenotypic variation in various reports [4, [29][30][31][32][33]. In this study, the effect of the rust resistance QTL at the Lr34 locus was consistent with previous reports [4,34].…”
Section: Discussionsupporting
confidence: 91%
“…Table.1 Molecular markers for foreground selection of rust resistance genes used in the study Chhuneja et al, (2011). This kind of interaction where the combination of genes give higher level of resistance than when present separately have been reported earlier by several authors (Kolmer et al, 1991;Kloppers and Pretorius 1997;Dyck and Samborski 1982) and often forms the basis of durable resistance.…”
Section: Resultssupporting
confidence: 69%
“…Some of the early work on the Lr34 phenotype, which showed that the gene is detectable in seedlings at low temperatures and that several resistance components interact in adult plants, was done in South Africa (Drijepondt & Pretorius, 1989;1991;Pretorius et al, 1994). In addition, Kloppers and Pretorius (1997) quantified the effect of gene combinations involving Lr13, Lr34 and Lr37 in reducing leaf rust infection in adult plants. 1991until 1996Wheat Board, 1998until 2008 South African Grain Laboratory.…”
Section: Wheat Rustsmentioning
confidence: 99%